A unified agent-based model to analyze organizational deviation and kaizen activities - Kobayashi, Tomomi; Takahashi, Satoshi; Kunigami, Masaaki; Yoshikawa, Atsushi; Terano, Takao (Proceedings of the 10th international conference on Advanced Agent Technology, 2012)
This paper presents a new agent based model for unifying organizational deviation and Kaizen activities. Deviation and Kaizen are both activities in business firms to break standards in operations. In the model, we have assumed that the former and the latter are only different in terms of external utilities, but both are agents' behavioral rules. Under the assumptions, we have developed a unified model and conducted simulations. The results show organizational deviation, Kaizen, and stagnation phenomena that are caused by the change of utility landscapes, diversity of agents, and reward distribution system. We have suggested the harnessing mechanism of deviation and Kaizen based on the experiment results. The experiment results have presented that Kaizen phenomena tend to emerge on the consistent utility landscape and diversified organization. They have also suggested that the excessive result-based reward could be a cause of prompting organizational deviation.